Phase II study of bevacizumab in combination with docetaxel and radiation in locally advanced squamous cell carcinoma of the head and neck. Issue 11 (29th October 2014) - Yao, Min; Galanopoulos, Nicholas; Lavertu, Pierre; Fu, Pingfu; Gibson, Michael; Argiris, Athanassios; Rezaee, Rod; Zender, Chad; Wasman, Jay; Machtay, Mitchell; Savvides, Panos
Abstract Background The purpose of this study was to establish the efficacy and toxicities of concurrent bevacizumab and docetaxel with radiation for locally advanced head and neck squamous cell carcinoma (HNSCC). Methods Patients with previously untreated HNSCC received standard daily radiotherapy (RT) with concurrent weekly docetaxel (20 mg/m2) and biweekly bevacizumab (5 mg/kg). Biweekly bevacizumab was then continued for up to 1 year after RT. The primary objective was progression‐free survival (PFS). Secondary objectives included overall survival (OS), patterns of failure, and toxicities of treatment. Results Thirty patients were recruited. With median follow‐up of 38 months, the 3‐year PFS, OS, locoregional recurrence‐free survival, and distant metastasis‐free survival was 61.7%, 68.2%, 84.5%, and 80.5%, respectively. The most common local toxicities were mucositis and dermatitis. Two patients developed hemorrhage. There was no grade 5 toxicity. Conclusion The combination of bevacizumab, docetaxel, and RT is tolerable and effective in HNSCC. This regimen is worthy of further study in appropriate subset of patients receiving chemoradiation therapy. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1665–1671, 2015